UPAYA GURU BIMBINGAN DAN KONSELING MEMPERSIAPKAN PESERTA DIDIK DALAM MEMILIH SEKOLAH LANJUTAN DI SMP NEGERI KOTA PADANG (Jurnal Pelangi : Research of Education and Development, 2015)
Unit secondary education has an important role in helping the success of the students in choosing a school . For the process of implementation of the service is focused on the field of personal development and learning of learners . This study aims to reveal , describe and analyze the efforts of BK teachers prepare students in select schools . This study included descriptive analysis with quantitative approach. 30 samples from 8 school teachers BK SMP Padang selected by purposive sampling technique . Instruments used the Likert scale model . Data were analyzed using simple statistical techniques  (techniques percentage) . Based on the findings of this study concluded efforts BK teachers prepare students in select schools in the category enough . Thus the efforts of teachers needs to be improved BK BK service program and service implementation BK.